(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The article examines the main occasions for public self-representations by professions related to health in antiquity: physicians and manufacturers and sellers of medicines. While today, thanks to the wide range of credentials, a medical doctor does not need to personally gain the confidence of the patient too much, his white coat does the most part of this task for him, in antiquity, those who practiced medical professions had to constantly demonstrate their skills, involving for this purpose their own or other’s bodies.